Executive Committee Minutes 2017-09-21 - Academic Senate:::::::::
Agenda approved. Minutes of 9/7/17 approved. Chair Report. President Report. Provost Report. Revision to Economics minor approved for the consent calendar. Strategic Planning dialog. EPC Report. Statewide Senator Report. Vice President of Student Affairs Report (question). ILOs (Institutional Learning Outcomes) discussion. Follow up on Senate discussions of RSCA and EO 1100 and EO 1110. Senate agenda approved.